Providing Healthcare Services at Home-A Necessity in Iran: A Narrative Review Article - Alireza NIKBAKHT-NASRABADI; Maryam SHABANY-HAMEDAN (Tehran University of Medical Sciences, 2016)
Background: Increasing hospital costs and its social and cultural problems has led to the idea of providing healthcare services at home. Because of infrastructural and implementation problems, providing healthcare at home in Iran has not been initiated yet. Therefore, this study set out to elaborate the need for a comprehensive system in order to provide this service in Iran. Methods: All articles published in indexing sites with the defined keywords in English or Farsi were gathered. The indexing websites included Iran Medex, PubMed Central, Elsevier journals, WHO publications and Google scholar from 1985 to 2014 were surveyed. Other documents included the related books and regulations. Results: Despite of having dominant religious values and constitution laws related to stability of family relations and establishment of clinical services and health care at home in Iran, providing health care services faces some harsh challenges including ignoring entrepreneurship and lack of required infrastructures such as lack of required insurance regulations, the inappropriate and indifferent performance of some activists home services and absence of registration and identification system in this domain. Conclusion: Because of the increasing number of elderly people in Iran and healthcare costs becoming more and more expensive, establishing a system for providing healthcare at home is inevitable.